Business Process Reengineering: Enhancing Efficiency and Data Accuracy Through QR Label Printing in Manufacturing - Igo Fatahilah Ilham; Wildan Sudarso (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
In the manufacturing industry, manual data management and label printing often result in significant time wastage and a high risk of data entry errors. This study aims to reengineer the business processes in a QR label printing and data storage system to achieve greater efficiency and integration. The applied method is Business Process Reengineering (BPR), which includes process analysis using ASME standards, throughput efficiency measurements, and the implementation of an information technology-based system called Ezylabel. The results show that the manual label printing process, which initially took 67 minutes due to excessive typing and manual Excel input, was reduced to only 14 minutes through the implementation of the Ezylabel application. Throughput efficiency increased from 65.67% to 68.49%. This study shows that technology-based BPR effectively eliminates non-value-added activities, accelerates workflows, and ensures data integrity in the production process, providing a scalable solution to modern manufacturing challenges.